2007
DOI: 10.1111/j.1469-1809.2007.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Microsatellite Polymorphisms of the Human 14q13.2 Region with Type 2 Diabetes Mellitus in Latvian and Finnish Populations

Abstract: SummaryA polymorphic microsatellite in intron 6 of the human proteasome core particle PSMA6 gene (HSMS006), and four other microsatellites localized upstream on human chromosome 14q13.2 (HSMS801, HSMS702, HSMS701, HSMS602), were genotyped in 104 type 2 diabetic patients and 129 age-matched control subjects from Latvia and replicated in 91 type 2 diabetic patients and 88 age-matched healthy control subjects from the Botnia Study in Finland. In type 2 diabetic patients from both populations the HSMS006 (TG)22 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…To support this idea, there is the fi nding that a variable number of TG repeats present in intron 8 of CFTR gene contributes to phenotype diversity in Cystic Fibrosis by forming RNA secondary structures that alter exon 9 splicing process (21). Linkages of TG repeats within intronic regions of different genes, including PAX7 which belongs to the same PAX6 gene family, have been described in a few diseases (22)(23)(24). Therefore, it is possible that nucleotide alterations within introns might have effects in transcript productions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support this idea, there is the fi nding that a variable number of TG repeats present in intron 8 of CFTR gene contributes to phenotype diversity in Cystic Fibrosis by forming RNA secondary structures that alter exon 9 splicing process (21). Linkages of TG repeats within intronic regions of different genes, including PAX7 which belongs to the same PAX6 gene family, have been described in a few diseases (22)(23)(24). Therefore, it is possible that nucleotide alterations within introns might have effects in transcript productions.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, PAX6 alleles bear a sequence of (TG) [19][20][21][22][23][24][25][26][27][28][29] repeats interrupted by a GG dinucleotide and followed by a (TG) 7 repeat. Patients A and C were heterozygous for (TG) 19/21 -GG -(TG) 7 sequences, however patient B was heterozygous for (TG) 16/19 repeats with absence of the intercalated GG dinucleotide and the last (TG) 7 repeats (Table 3).…”
Section: Molecular Studiesmentioning
confidence: 99%
“…1) as well as to that previously described for the Latvian and Finnish populations (Sjakste et al, 2004(Sjakste et al, , 2007. In the current study, we identified 7 alleles of HSMS602 (167-171 bp and 177-178 bp), 9 alleles of HSMS701 [(AC) 5 AT(AC) 14-12 ], 12 alleles of HSMS702 [(TG) 10-14, 17-18, 20-25 Figure 1 summarizes data of the remaining allele's distribution in JIA patients and control subjects.…”
Section: Allele Presentation and Association Analysismentioning
confidence: 97%
“…To improve the reliability of our data, formerly based mostly on fragment size analysis (Sjakste et al, 2004(Sjakste et al, , 2007, we have checked the MS motifs by sequencing. Genomic regions encompassing MS repeats were amplified and sequenced in several specimens to annotate the MS length variability to MS repeat number variation.…”
Section: Ms Motif Variabilitymentioning
confidence: 99%
See 1 more Smart Citation